Pentingnya Penguatan Sistem Hukum Nasional dan Antikorupsi Bagi Siswa/I Sekolah Menengah Atas Negeri di Jakarta - Naomi M. G., Juniartha Gladys; Rajagukguk, Elisabeth Immanuella; Purba, Eugenia Priscilla; Prakosa, Reza Bintang; Boantua M., Yuris Utrecht; Purwa, Rumi Alghozali; Pasha, Anindya; Alfarisi, Rafi; Ismail, Umar Jafar; Tarina, Dwi Desi Yayi; S, Satino; S, Suprima; Manalu, Ronald (Media Hukum Indonesia (MHI), 2024)
Program Kreatif Mahasiswa (PKM) examine the importance of strengthening the national legal system and anti-corruption for SMA Negeri 2 Jakarta ,the nasional legal system in indonesia which is based on Pancasila and UUD 1945, , functions as a framework that regulates the life of society and the state. In this context, education about the legal system is important to provide students with an understanding of their rights and obligations as citizens. This knowledge not only creates legal awareness, but also encourages active participation in law enforcement and social justice. In addition, anti-corruption education in schools is a strategic step to build the character of the younger generation with integrity. Corruption is a serious problem that damages the social and economic order of society based on Article 3 of Law 31/1999 jo. Constitutional Court No.25/PUU-XIV/2016. Through education integrated with anti-corruption values, students are taught to understand the consequences of corrupt acts as well as the importance of honesty, transparency and accountability. With this approach, it is hoped that students will not only understand the importance of the legal system and personal integrity but also be able to contribute to creating a more just society free from corrupt practices. Education is a long-term investment for the future of the nation, forming individuals who are not only academically intelligent but also have high morality.